Distributions and Conservation Status of Carrot Wild Relatives in Tunisia: A Case Study in the Western Mediterranean Basin - Mezghani, Najla; Khoury, Colin K.; Carver, Daniel; Achicanoy Estrella, Harold Armando; Simon, Philipp; Martínez Flores, Fernando; Spooner, David (Wiley, 2019)
Crop wild relatives, the wild progenitors and closely related cousins of cultivated plant species, are sources of valuable genetic resources for crop improvement. Persisting gaps in knowledge of taxonomy, distributions, and characterization for traits of interest constrain their expanded use in plant breeding and likewise negatively affect ex situ (in genebanks) and in situ (in natural habitats) conservation planning. We compile the state of knowledge on the taxonomy and distributions of the wild relatives of carrot (genus Daucus L.) natively occurring within Tunisia—a hotspot of diversity of the genus, containing 13 taxa (27% of species worldwide). We use ecogeographic information to characterize their potential adaptations to abiotic stresses of interest in crop breeding and assess their ex situ and in situ conservation status. We find substantial ecogeographic variation both across taxa and between populations within taxa, with regard to adaptation to high temperatures, low precipitation, and other traits of potential interest. We categorize three of the taxa high priority for further conservation both ex situ and in situ, five medium priority, and five low priority, with none currently considered sufficiently conserved. Geographic hotspots for species diversity, especially in the northern coastal areas, represent particularly high value regions for efficient further collecting for ex situ conservation and for in situ protection in Tunisia.